Cecil B. DeMille a life in art - Louvish, Simon 1947- (Dunne Books [u.a.], 2008)
Examines the life and work of the motion picture director best known for his biblical sagas, including "Samson and Delilah" and "The Ten Commandments," discussing his complex personal life and the paradoxes existing within his films.